Penerapan Model Pembelajaran Picture and Picture pada Siswa Kelas II SDN Rancailat 1 Kabupaten Tangerang - Magdalena, Ina; Melyana, Angele; Agustin, Renny (Lembaga Yasin AlSys, 2023)
This Picture and Picture learning model is a learning model that uses picture media in the teaching and learning process. Overall, the purpose of this research is to find out and develop active learning in class II students at SDN Rancailat 1 Tangerang Regency by applying the Picture and Picture model. This research is (CAR) or Classroom Action Research. After doing research, it is known that learning using the Picture and Picture learning model goes very well. Judging from the initial conditions, cycle I and cycle II the class average value increased. The class average in the initial conditions of 64.56 increased to 69.56 in cycle I, and increased again to 72.88 in cycle II. Furthermore, the achievement of student graduation increased, as many as 27 students (56.25%) in the initial conditions, increased to 40 students (83.33%) in cycle I, and to 45 students (93.75%) in cycle II.